Tragal cartilage tympanoplasty results - KARAMAN, Emin; YILMAZ, Süleyman; ÖĞREDEN, Şahin; ACIOĞLU, Engin; ENVER, Özgün (Cerrahpaşa Medical Journal, 2019)
To investigate the pre-operative, post-operative airway hearing threshold levels and post-operative perforation closure rates in type 1 tragal cartilage tympanoplasty done patients. We perform endaural approach underlay technique primary tragal cartilage type 1 tympanoplasty to 14 patients who has hearing impairment and otorhea. We find pre-operative and 2 years after operation airway hearing threshold levels at 500, 1000, 2000, 4000 Hz frequencies. Also we investigate post-operative perforation closure rates. The mean airway hearing gain at 500 Hz in 13 patients was 13.84 dB, it was 11 dB at 1000Hz in 10 patients, the mean airway hearing gain at 2000 Hz was 11.36 dB in 11 patients and it was 10.45 dB at 4000 Hz in 11 patients.We find our postoperative perforation closure rate as % 92,85. We concluded that we can choose tragal cartilage tympanoplasty technique in primary chronic otitis media patients and we see that our airway hearing gain and perforation closure rates are very good.